Financial Education Programme (Institutional Knowledge at Singapore Management University, 2000)
Sunil Sreenivasan, SMU trustee and Citibank's country corporate officer, speaking to Singapore Management University undergraduates on 9 October 2000. His lecture was the first in a financial education programme which is supplementary to the SMU core curriculum. It provides practical lessons in finance, banking and economics.